Python crash course : a hands-on, project-based introduction to programming - Matthes, Eric, 1972- (No Starch Press, 2016)
"A project-based introduction to programming in Python, with exercises. Covers general programming concepts, Python fundamentals, and problem solving. Includes three projects - how to create a simple video game, use data visualization techniques to make graphs and charts, and build an interactive web application"--